2021
DOI: 10.1044/2021_jslhr-20-00739
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Response Inhibition in Adults Who Stutter

Abstract: Purpose Adults who stutter (AWS) often attempt, with varying degrees of success, to suppress their stuttered speech. The ability to effectively suppress motoric behavior after initiation relies on executive functions such as nonselective inhibition. Although previous studies found that AWS were slower to inhibit manual, button-press response than adults who do not stutter (AWNS), research has yet to confirm a consistent relationship between manual and verbal inhibition. No study has examined verbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…He also found that stuttering adults do not differ in terms of BIS/BAS from the control group. In turn, in Treleaven's and Coalson's study people who stuttered much slower inhibited inaccurate motor responses, but not verbal responses (Treleaven & Coalson, 2021).…”
Section: Discussionmentioning
confidence: 88%
“…He also found that stuttering adults do not differ in terms of BIS/BAS from the control group. In turn, in Treleaven's and Coalson's study people who stuttered much slower inhibited inaccurate motor responses, but not verbal responses (Treleaven & Coalson, 2021).…”
Section: Discussionmentioning
confidence: 88%
“…Simultaneously, experimental paradigm studies investigating motor or verbal response inhibition in children and AWS have produced mixed findings. Some researchers have reported that participants who stutter do not perform as well as controls, while others have reported comparable performances between the groups (Bakhtiar & Eggers, 2023;Eggers et al, 2018;Harrewijn et al, 2017;Piispala et al, 2016;Treleaven & Coalson, 2021).…”
Section: Inhibitory Control Cognitive Flexibility and The Production ...mentioning
confidence: 99%
“…Consistent with the account presented here, other researchers have associated this right hemisphere activation during stuttering with activation of the IFG-STN hyperdirect pathway (Arenas, 2017; Neef et al, 2018). Adults who stutter are not impaired in their ability to inhibit verbal responses (Treleaven & Coalson, 2021), but may exhibit widespread hyperactivity across neural correlates of inhibitory control (Wiltshire et al, 2020). This hyperactivity of inhibitory control in adults who stutter may explain previous findings of faster response times compared to those of fluent controls during cognitive conflict (Subramanian & Yairi, 2006).…”
Section: How Do Stuttering-like Disfluencies Develop?mentioning
confidence: 99%
“…Neural connectivity of the right hemisphere inhibitory network underlying hyperdirect pathway activation increases with stuttering severity (Neef et al, 2018). Faster verbal response inhibition in adults who stutter is also associated with greater physical concomitants of stuttering (Treleaven & Coalson, 2021). Stuttering severity may be related to the speed in which the hyperdirect pathway freezes the speech motor system in the face of cognitive conflict.…”
Section: What Explains Variability In Treatment Effectiveness For Peo...mentioning
confidence: 99%